Indicative traits of aluminium sensibility in rice. I. Growth in nutrient solution - Vicente, Fabiano Mascarenhas Paulo; Rossiello, Roberto Oscar Pereyra; Pereira, Maurício Ballesteiro (Pesquisa Agropecuaria Brasileira, 1998)
In this experiment, it was evaluated the sensibility of several rice (Oryza sativa L.) plant traits (leaf area, LA; root area, RA; maximum root length, RL; maximum leaf length, LL; root number, RN; root dry weight, RDW; shoot dry weight, SDW) at different Al levels (0, 10, 20 e 30 mg L-1) in nutrient solution, aiming to establish a sequential response order. Trait values were represented by averaged values of 20 genotypes. Twenty days old seedlings were transferred to nutrient solution at pH 4.0 and arranged in a random design with four replications. Results were expressed as relative yield (RY%). Regression equations were fitted according to an exponential model between RY values (except for RN RY which did not show any response) and Al added levels. Sensibility order was deduced by paired t-test comparisons from b coefficients. It was concluded that RA RY resulted the most sensible indicator, closely followed by LA RY and RL RY. On the other extreme, LL RY resulted the least sensible trit while RDW RY and SDW RY showed intermediate sensibility.